Effect of Price Determinants on World Cocoa Prices for Over the Last Three Decades: Error Correction Model (ECM) Approach - Lya Aklimawati; Teguh Wahyudi (Indonesian Coffee and Cocoa Research Institute, 2013)
High volatility cocoa price movement is consequenced by imbalancing between power demand and power supply in commodity market. World economy expectation and market liberalization would lead to instability on cocoa prices in the international commerce. Dynamic prices moving erratically influence the benefit of market players, particularly producers. The aim of this research is (1) to estimate the empirical cocoa prices model for responding market dynamics and (2) analyze short-term and long-term effect of price determinants variables on cocoa prices. This research was carried out by analyzing annualdata from 1980 to 2011, based on secondary data. Error correction mechanism (ECM) approach was used to estimate the econometric model of cocoa price.The estimation results indicated that cocoa price was significantly affected by exchange rate IDR-USD, world gross domestic product, world inflation, worldcocoa production, world cocoa consumption, world cocoa stock and Robusta prices at varied significance level from 1 - 10%. All of these variables have a long run equilibrium relationship. In long run effect, world gross domestic product, world cocoa consumption and world cocoa stock were elastic (E >1), while other variables were inelastic (E <1). Variables that affecting cocoa pricesin short run equilibrium were exchange rate IDR-USD, world gross domestic product, world inflation, world cocoa consumption and world cocoa stock. The analysis results showed that world gross domestic product, world cocoa consumption and world cocoa stock were elastic (E >1) to cocoa prices in short-term. Whereas, the response of cocoa prices was inelastic to change of exchange rate IDR-USD and world inflation.Key words: Price determinants, cocoa, Error Correction Model, demand, supply, stock